Silicon mediated improvement in Agronomic traits, physiological parameters and fiber content in Oryza sativa - Dorairaj, Deivaseeno; Ismail, Mohd Razi; Sinniah, Uma Rani; Tan, Kar Ban (Springer, 2020)
Silicon, a quasi-essential element that is often associated with rigidity and hardiness is an alleviator of biotic and abiotic stresses. Lodging affects the ability of plants especially cereal plants such as rice, Oryza sativa to grow upright, thus reducing yield and increasing harvesting costs. Bending or lodging resistance could be increased by strengthening the rice culm. Here, we tested stage and method of silicon application, each with three levels of treatments to find the right combination to enhance yield and lodging resistance in MR219, a popular rice variety in Malaysia. Application of silicon at the onset of reproductive stage via topdressing improved agronomic and physiological parameters. Plants applied with Si at the reproductive stage by means of topdressing showed a significantly higher leaf area. Number of tillers, weight per panicle and weight of 100 grains were significantly higher when silicon was applied as topdressing at the reproductive stage. Number of spikelets per panicle was significantly higher when silicon was supplied as topdressing or soil incorporation. Percentage of filled spikelets was significantly higher when silicon supplementation was done as topdressing at either reproductive or maturity stages. Mode of application which favoured the increase in soluble lignin and neutral detergent fiber was topdressing and soil incorporation. Meanwhile, cellulose and acid detergent lignin was highest when silicon was applied at the reproductive and maturity stages. Application of silicon at the reproductive stage by means of topdressing was effective in improving growth, yield and stem strength of the rice plant since the method has higher retention time and has residual effect. Foliar application was deemed unsuitable as it can only be applied in minimal amount while showing a temporary effect.